4, 5 caffeoylquinic acid and scutellarin, identified by integrated metabolomics and proteomics approach as the active ingredients of Dengzhan Shengmai, act against chronic cerebral hypoperfusion by regulating glutamatergic and GABAergic synapses. (February 2020) - Sheng, Ning; Zheng, Hao; Li, Min; Li, Menglin; Wang, Zhe; Peng, Ying; Yu, Haibo; Zhang, Jinlan
Graphical abstract: Abstract: Dengzhan Shengmai (DZSM) is a proprietary Chinese medicine for remarkable curative effect as a treatment of cerebrovascular diseases, such as chronic cerebral hypoperfusion (CCH) and dementia based on evidence-based medicine, which have been widely used in the recovery period of ischemic cerebrovascular diseases. The purpose of this study was to investigate the active substances and mechanism of DZSM against CCH. Integrative metabolomic and proteomic studies were performed to investigate the neuroprotective effect of DZSM based on CCH model rats. The exposed components of DZSM in target brain tissue were analysed by a high-sensitivity HPLC-MS/MS method, and the exposed components were tested on a glutamate-induced neuronal excitatory damage cell model for the verification of active ingredients and mechanism of DZSM. Upon proteomic and metabolomic analysis, we observed a significant response in DZSM therapy from the interconnected neurotransmitter transport pathways including glutamatergic and GABAergic synapses. Additionally, DZSM had a significant regulatory effect on glutamate and GABA-related proteins including vGluT1 and vIAAT, suggested that DZSM could be involved in the vesicle transport of excitatory and inhibitory neurotransmitters in the pre-synaptic membrane. DZSM could also regulated the metabolism of arachidonic acid (AA), phospholipids, lysophospholipids and the expression of phospholipase A2 in post-synaptic membrane. The results of glutamate-induced neuronal excitatory injury cell model experiment for verification of active ingredients and mechanism of DZSM showed that there are five active ingredients, and among them, 4, 5 caffeoylquinic acid (4, 5-CQA) and scutellarin (SG) could simultaneously affect the GABAergic and glutamatergic synaptic metabolism as well as the related receptors, the NR2b subunit of NMDA and the α1 subunit of GABAA . The active ingredients of DZSM could regulate the over-expression of the NMDA receptor, enhance the expression of the GABAA receptor, resist glutamate-induced neuronal excitatory damage, and finally maintain the balance of excitatory and inhibitory synaptic metabolism dominated by glutamate and GABA. Furtherly, we compared the efficacy of DZSM, 4, 5-CQA, SG and the synergistic effect of 4, 5-CQA and SG, and the results showed that all the groups significantly improved cell viability compared with the model group (p < 0.001). The western blot results showed that DZSM, 4, 5-CQA, SG and 4, 5-CQA/SG co-administration groups could significantly regulate the expression of receptors (GABAA α1 and NR2b subunit of NMDA) and synaptic-related proteins, such as Sv2a, Syp, Slc17a7, bin1 and Prkca, respectively. These results proved DZSM and its active ingredients (4, 5-CQA and SG) had the effect of regulating glutamatergic and GABAergic synapses. Finally, membrane potential FLIPR assay of 4, 5-CQA and SG was used for GABRA1 activity test, and it was found that the two compounds could increase GABA-induced activation of GABRA1 receptor (GABA 10 μM) in a dose-dependent manner with EC50 value of 48.74 μM and 29.77 μM, respectively. Manual patch clamp method was used to record NMDA NR1/NR2B subtype currents, and scutellarin could cause around 10 % blockade at 10 μM (p＜0.05 compared with the control group). These studies provided definitive clues of the mechanism for the neuroprotective effect of DZSM for CCH treatment and the active compounds regulating glutamatergic and GABAergic synapses. Additionally, 4, 5-CQA and SG might be potential drugs for the treatment of neurodegenerative disease related to CCH.